2022
DOI: 10.3390/agriculture12122006
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Supplemental Feeding on Body Condition Score and Reproductive Performance Dynamics in Botosani Karakul Sheep

Abstract: The aim of this research was to study the impact of supplementary feeding on reproductive traits in sheep. Two groups, L1 (control) and L2 (experimental treatment), of adult females aged between two and six years belonging to the Botosani Karakul sheep breed were formed. The experimental treatment group (L2) received supplementary feeding 25 days prior to mating. Improvements in body condition and significant increases in live weight occurred by the time of mating in those ewes that had been flushed (L2) (p &l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 43 publications
2
7
0
Order By: Relevance
“…Similar results were found, suggesting that the poor BCS caused by a decrease in nutrient uptake induces sub-nutrition, diminishing the endometrial sensitivity to progesterone and affecting embryo survival [32]. Generally, a greater BCS at mating leads to an increased probability to manifest estrus and a higher ovulation rate, and subsequently, to a higher percentage of lambing potential [32,34]. Many researchers have reported that fertility is affected by BCS, and higher fertility rates were recorded for females with BCSs between 2 and 4 [38].…”
Section: Reproductive Performances Of Ewessupporting
confidence: 76%
See 3 more Smart Citations
“…Similar results were found, suggesting that the poor BCS caused by a decrease in nutrient uptake induces sub-nutrition, diminishing the endometrial sensitivity to progesterone and affecting embryo survival [32]. Generally, a greater BCS at mating leads to an increased probability to manifest estrus and a higher ovulation rate, and subsequently, to a higher percentage of lambing potential [32,34]. Many researchers have reported that fertility is affected by BCS, and higher fertility rates were recorded for females with BCSs between 2 and 4 [38].…”
Section: Reproductive Performances Of Ewessupporting
confidence: 76%
“…Ewes having a low BCS have higher prenatal and neonatal mortalities [37] and a lower survival rate. Similar results were found, suggesting that the poor BCS caused by a decrease in nutrient uptake induces sub-nutrition, diminishing the endometrial sensitivity to progesterone and affecting embryo survival [32]. Generally, a greater BCS at mating leads to an increased probability to manifest estrus and a higher ovulation rate, and subsequently, to a higher percentage of lambing potential [32,34].…”
Section: Reproductive Performances Of Ewessupporting
confidence: 66%
See 2 more Smart Citations
“…The figures represent the important to evaluate BCS, because of their strong correlation with reproduction traits. Likewise, the influence of supplement feeding to adult Botosani Karakul ewes 25 days prior to mating and showed that BCS increased significantly, the number of lambs per individual parturition improved as BCS increase and therefore influence their economic values [13].…”
Section: Discussionmentioning
confidence: 99%